北半球の季節海氷域の初冬海氷面積の予測可能性 - 中野渡, 拓也; Nakanowatari, Takuya (2016)
近年、北半球中緯度の気候に対する北極域の海氷変化の影響が注目されている [e.g., Frankignoul et al. 2014]。特に、日本を含むユーラシア大陸では2005/06, 2011/12, 2012/13、北アメリカでは2009/10, 2010/11, 2013/14などに厳冬イベントが頻発しており、その原因として、それぞれバレンツ海やベーリング海などの風上に位置する海氷域の減少傾向に伴う大気の熱源応答の影響が指摘されている[e.g., Mori et al. 2014]。そこで、海洋から大気への熱輸送が著しい初冬（11－12月）におけるこれらの海域の海氷面積の経年変動の要因について、海洋の水平熱輸送の影響に着目した研究を行ってきた。その結果、海水温の情報を用いることによって、バレンツ海では約1年前、ベーリング海では2－3ヶ月前の時点で有意な予測スキルが見込まれることが示唆された。本発表では、これらの研究のレビューを行うと共に、今後の課題について議論する。 Recently, a number of studies focus on the influence of sea ice change in the Arctic Ocean and its relation to winter climate in the mid-latitude [e.g., Frankignoul et al. 2014]. Along with the recent sea ice decrease, the Eurasia continent and North America have experienced abnormally cold winters in recent years (2005/06, 2011/12, 2012/13 for Eurasia and 2009/10, 2010/11, 2013/14 for North America), which is likely to attribute to the atmospheric responses to the reduced sea ice zones [Mori et al. 2014]. To assess the causes of sea ice variability in early winter (November-December), where surface heat fluxes is prominent, we have examined the role of ocean heat advection on seasonal forecasting of sea ice area based on atmosphere and ocean datasets during several decades. The statistical analysis suggests that the interannual variability of sea ice area in these regions can be skillfully predicted by using ocean temperature data at the stage of 3 months to 1 year ahead. In this seminar, we will review these studies and discuss the remaining issues. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：7月20日（水）10:00-10:50 場所：C301（3階セミナー室） conference object